Cystic Lung Disease as a Sequela of Severe COVID-19: Case Series. (April 2022) - Patti, Ravi Karan; Dalsania, Nishil; De Araujo Duarte, Claudia; Randhawa, Gurchetan; Somal, Navjot; Kupfer, Yizhak
Coronavirus disease 2019 (COVID-19) presented in December 2019 and has persisted since. The global pandemic has given rise to a novel acute disease process with a continually rapidly increasing prevalence of chronic disease and associated complications. There is minimal information on the long-term pulmonary complications of this disease. We present a series of 9 patient case reports and their respective imaging admitted with COVID-19 acute respiratory distress syndrome (ARDS) to highlight the cystic lung disease complications which may arise due to severity and disease progression. Our aim is to raise awareness of the sequela of COVID-19 ARDS, including its potentially catastrophic long-term consequences to the respiratory tract involving cystic lung disease.